2014
DOI: 10.3399/bjgp14x677842
|View full text |Cite
|
Sign up to set email alerts
|

Oral penicillin prescribing for children in the UK: a comparison withBNF for Childrenage-band recommendations

Abstract: BackgroundThe British National Formulary for Children (BNFC) recommends dosing oral penicillins according to age-bands, weight-bands, or weight-based calculations. Because of the rising prevalence of childhood obesity, age-band-based prescribing could lead to subtherapeutic dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…Recent observational studies have also identified that suboptimal dosing of antibacterial and antiviral drugs in children is similarly prevalent. Saxena et al (26), reporting prescribing surveillance data from the United Kingdom, identified that children and adolescents prescribed oral penicillin received doses below the national recommendations in 40% and 70% of cases, respectively. Menson et al (27) described the widespread suboptimal dosing of antiretroviral drugs in children and identified several potential causes of error, including the inadequacy of pharmacokineticpharmacodynamic (PK-PD) data.…”
Section: Discussionmentioning
confidence: 99%
“…Recent observational studies have also identified that suboptimal dosing of antibacterial and antiviral drugs in children is similarly prevalent. Saxena et al (26), reporting prescribing surveillance data from the United Kingdom, identified that children and adolescents prescribed oral penicillin received doses below the national recommendations in 40% and 70% of cases, respectively. Menson et al (27) described the widespread suboptimal dosing of antiretroviral drugs in children and identified several potential causes of error, including the inadequacy of pharmacokineticpharmacodynamic (PK-PD) data.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the doses given for penicillin V and flucloxacillin are exactly the same in the UK, although flucloxacillin was licensed many years later. The dosing regimens for amoxicillin were also originally the same as penicillin V until the dose was recently doubled in older children after we demonstrated a mismatch in prescribing against the guidance 12. In a follow-up paper we modelled this phenomenon and found very little likelihood now of significant underdosing 13.…”
Section: The Impact Of the Early Penicillin V Dosing Regimens On Othementioning
confidence: 99%
“…In original discussions, it was decided to compare the doses of 125 mg and 250 mg, both three times per day (although the final trial design was based on weight-band dependent dosing). At that time, and in the absence of any randomised evidence, the British National Formulary specified a 250 mg dose, but surveys had shown that the 125 mg dose was more commonly used in clinical practice [ 6 , 7 ]. This raised the dilemma of which dose should be defined as standard and which as experimental.…”
Section: Non-inferiority or Superiority Which Is It?mentioning
confidence: 99%